Upaya Guru untuk Meningkatkan Motivasi Belajar Siswa Kelas IV pada SDN Pluit 03 Jakarta Utara - Nur Qur’ani Amanatullah; Abdul Halim (Departement of Mathematics Education, 2024)
The problems that occur are related to the learning motivation of students at SDN Pluit 03 North Jakarta class IV, how are the teacher's efforts to increase student learning motivation in class, starting from the beginning of teaching to the end if the teacher explains and if there are students who don't listen or pay attention to the teacher will ask what earlier the teacher was explaining, if they don't know the teacher will advise them and provide motivation to students who have not paid attention and the teacher also uses interesting learning methods so that students are not bored and bored, students must have motivation, someone will get the desired results in learn if He has the will to learn. Motivation can act as a motivation to achieve good results. Someone will do an activity because they have motivation from within which is usually called intrinsic motivation. having high learning motivation will achieve the best results. the results of this study find out how the efforts made by the teacher to increase student learning motivation. The analysis obtained shows that as many as 28 students, of which 2 lack motivation to learn and also still like to joke in class and pay little attention to the teacher.